Estimation of the Forecasted Cargo Flow of an Inter-/multimodal Transport and Logistics Center - Myronenko, V. K.; Ziubryk, Y. O. (Science and Transport Progress, 2025)
Purpose. The study is aimed at obtaining new knowledge about the patterns of formation of cargo flows generated (induced) during the creation of transport and logistics centers serving multi / intermodal cargo transportation, using products and services of scientometric databases. The timeframe of the studied sources is 2010–2024. Methodology. To obtain relevant empirical data, the authors reviewed the literature and official websites of transport and logistics centers (TLCs) in the EU countries, which reflect data on their infrastructure and workloads in servicing various modes of transport. Findings. In the course of the work it was found that: 1) the studied set of TLCs of the EU countries can be clustered by the ratio «TLC area, ha – generated annual cargo flow per unit area of TLC, t/(m2-yr)»; 2) clusters of large, small and medium-sized (by area) TLCs can be conditionally distinguished; 3) as a rule, small TLCs generate more cargo per unit area, which sets the goal for further research – to determine the optimal area and other parameters of TLCs according to the criterion of its maximum specific productivity per unit area. Scientific originality. For the first time, the authors obtained quantitative dependencies of the ratio of «TLC area, ha – generated annual cargo flow per unit area of TLC, t/(m2-yr)», which have the character of a decreasing power function for small and medium-sized TLCs and a decreasing linear function for large (by area) TLCs. Practical value. Based on the results obtained, it is possible to predict the size of the generated cargo flow depending on the selected design solutions when creating new TLCs, which will increase the reliability of feasibility studies for relevant investment projects. These studies can also be useful in the educational process in the areas of «Railway Transport», «Transport Technologies», «Construction and Design of Transport Infrastructure», in the study of the disciplines «Multimodal Freight Transportation», «Logistics of International Freight Transportation», organization of scientific and practical seminars, advanced training courses, etc.